Kombinasi Algoritma Cipher Block Chaining dan Triangle Chain Cipher dalam Penyandian File Text - Nurul Hapifah Purba (Bulletin of Computer Science Research, 2022)
Currently the use of information technology as a medium of information exchange is growing very widely. Various types of information such as text, images, sound and video can be converted into digital media that allows it to be reproduced or transmitted through various media. One of them is the internet, through the internet we can easily exchange information with other people in various places. However, there are times when information/messages are confidential, where no other party may know the contents of this information other than the sender and recipient. So we need a security against the message. Cryptography is a technique and art to encode messages or information in a medium, such as text, images, audio or video which aims to avoid suspicion from unauthorized people. For that we need a software that can encode confidential information in a text file. However, in hiding messages in text files using cryptography alone is not necessarily safe, so a useful algorithm is needed to improve security, therefore Cipher Block Chaining and Triangle Chain Cipher algorithms are needed. The research objective is to apply the Cipher Block Chaining and Triangle Chain Cipher algorithms for text file encoding applications. This is necessary because it often happens that the text message sent is a secret message that should not be known to just anyone. Block Chaining Ciphers and Triangle Chain Ciphers are useful algorithms to provide an advantage in terms of increased security in text files.